Flaxseed Characteristics and Using Cake Mucilage in Pan Bread - Muhammad, E. Elsorady; Elsayed, A.A. Hendawy; Sahar, S. El-Gohery (Food Technology Research Journal, 2024)
The main objective of this study was to evaluate the characteristics of flaxseed and to investigate the effects of using different levels of flaxseed cake mucilage (FCM) as a substitute for bread improver (0.5%, 1.0%, and 1.5%) or as a replacement for oil (33.33%, 66.66%, and 100%) on the sensory attributes, physical characteristics, color, texture profile, and freshness of pan bread. The results indicated that the Sakha 5 flaxseed variety had an oil content of approximately 33.37%, with linolenic acid as the primary fatty acid, comprising about 57.47% of the total. Flaxseed cake mucilage (FCM), extracted from the by-product of flaxseed oil production, is composed of natural and acidic sugars, and it exhibits excellent water-binding and rheological properties. Sensory evaluation data revealed that the complete replacement of bread improver with FCM at the 1.0% level enhanced the color, texture, taste, general appearance, and overall acceptability of the pan bread, compared to samples using FCM at 0.5% and 1.5% levels. Additionally, partial replacement of oil with FCM at the 66.66% level improved crumb color and texture without a significant difference in overall acceptability when compared to the control pan bread. The physical characteristics of the bread showed a reduction in volume and specific volume in samples containing FCM compared to the control. However, the inclusion of FCM in pan bread formulation delayed staling and improved freshness due to its ability to retain moisture in the crumb. In conclusion, FCM shows potential as a functional ingredient in pan bread production. Further studies are recommended to explore additional applications of FCM in various baked products.